2003
DOI: 10.1016/s0141-0229(03)00219-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of free water on enzyme activity in immobilized lipase-catalyzed reactions in organic solvents

Abstract: The influence of water content on the lipase-catalyzed acidolysis of triolein (glycerol-trioleate, TO) and caprylic acid (CA) in hexane, using an immobilized enzyme was studied. An adequate water content (R W ) ranged from near zero to 0.1 g of water/g of dry enzyme. Over these values there was a decrease in the rate of incorporation of CA into triglyceride. This decrease was attributed to the progressive flooding of the carrier's pores, in which the enzyme was immobilized. The flooding reduced the number of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 25 publications
1
20
0
3
Order By: Relevance
“…Camacho et al 21 proposed a mechanistic model based on the elementary reactions that may occur in the process. In this work, a simple model similar to the one proposed by Oliveira et al 22 , has been considered.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…Camacho et al 21 proposed a mechanistic model based on the elementary reactions that may occur in the process. In this work, a simple model similar to the one proposed by Oliveira et al 22 , has been considered.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…Previously, it was suggested that the agglomeration of water might flood the enzyme pores, causing decreases in the reaction rates [30]. In this study, it was also shown that the presence of water at 4-5 % in ethanol cause some negative effects on the reusability of the biocatalyst.…”
Section: Accepted Manuscriptmentioning
confidence: 61%
“…The initial low conversion of the TAG and relative high amount of unreacted TAG quantified in the transesterified oils during the initial segment of the reaction may be due to a myriad of factors, such as initial delay in the transesterification reaction and may be due to minimal mixing and dispersion of the alcohol with oil, poor solvation, or low miscibility of TAG in the alcohol creating a two-phase/heterogeneous system, the deactivation effect of the polar ethanol on the enzyme, interfacial action of lipase, and the nature of lipase catalysis in non-aqueous media [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%